ChemInform Abstract: Investigation of Structural and Electronic Properties of Epitaxial Graphene on 3C‐SiC(100)/Si(100) Substrates. Issue 31 (August 2015) - Gogneau, Noelle; Trabelsi, Amira Ben Gouider; Silly, Mathieu G.; Ridene, Mohamed; Portail, Marc; Michon, Adrien; Oueslati, Mehrezi; Belkhou, Rachid; Sirotti, Fausto; Ouerghi, Abdelkarim
Abstract Review: 81 refs.